2014
DOI: 10.1371/journal.pone.0105376
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Role of Adverse Events in the Mortality Difference between First and Second-Generation Antipsychotics in Older Adults: Systematic Review and Meta-Synthesis

Abstract: BackgroundObservational studies have reported higher mortality among older adults treated with first-generation antipsychotics (FGAs) versus second-generation antipsychotics (SGAs). A few studies examined risk for medical events, including stroke, ventricular arrhythmia, venous thromboembolism, myocardial infarction, pneumonia, and hip fracture.Objectives1) Review robust epidemiologic evidence comparing mortality and medical event risk between FGAs and SGAs in older adults; 2) Quantify how much these medical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 70 publications
1
47
0
1
Order By: Relevance
“…Comparative data providing information about different SGAs are sparse, and in particular, the cardiovascular safety of newer SGAs, such as ILO, LUR, BRE, and CAR, is missing. In the elderly, higher mortality with FGAs than SGAs seems to be partially explained by a greater risk for stroke and AMI (in addition to ventricular arrhythmias and hip fracture) 121. Broadly, in SMI, HAL, CPZ, OLA, RIS, and QUE have shown the strongest association with cardiovascular events 69,122126.…”
Section: Methodsmentioning
confidence: 97%
“…Comparative data providing information about different SGAs are sparse, and in particular, the cardiovascular safety of newer SGAs, such as ILO, LUR, BRE, and CAR, is missing. In the elderly, higher mortality with FGAs than SGAs seems to be partially explained by a greater risk for stroke and AMI (in addition to ventricular arrhythmias and hip fracture) 121. Broadly, in SMI, HAL, CPZ, OLA, RIS, and QUE have shown the strongest association with cardiovascular events 69,122126.…”
Section: Methodsmentioning
confidence: 97%
“…CIs: 1.16-1.23] compared to atypical AP users (Jackson et al, 2014);however, this only identified two cohort studies. Another meta-analysis found a 1.88-fold higher likelihood [odds ratio (OR) = 1.88, 95% CIs: 1.39-2.54) of MI in AP users vs. non-users (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…First-generation antipsychotics have shown even higher mortality (1.4 fold) early after starting therapy, as when compared to second-generation antipsychotics in observational post-marketing studies. 3 These findings led the FDA to issue Black Box warnings. 4 …”
Section: Introductionmentioning
confidence: 99%
“…9 A systematic review of observational post-marketing studies using mostly administrative claims data compared risk of first- and second-generation antipsychotics for these medical events and concluded that stroke, hip fracture, myocardial infarction, and ventricular arrhythmia combined could explain between 17% and 42% of the mortality difference. 3 But this study was limited by its reliance on study-level data and published mortality rates.…”
Section: Introductionmentioning
confidence: 99%